Correlação entre tempo de trânsito oral e faríngeo no acidente vascular cerebral - Santos, Rarissa Rúbia Dallaqua Dos; Cola, Paula Cristina; Jorge, Adriana Gomes; Peres, Fernanda Matias; Lauris, José Roberto Pereira; Silva, Roberta Gonçalves Da (Academia Brasileira de Audiologia, 2015)
Purpose To correlate the total oral transit time (TOTT) with initiation of pharyngeal response (IPR) and pharyngeal transit time (PTT) in stroke.Methods The study included 61 swallowing videofluoroscopy exams of individuals after hemispheric ischemic stroke. Of these, 28 were male and 33 female, with ages ranging from 40 to 101 years (mean 65 years). For analysis of the results, individuals were divided into two groups. Group 1 (G1) consisted of 17 individuals with TOTT up to 2000 ms, as normality, and Group 2 (G2) consisted of 44 individuals with TOTT greater than 2000 ms. Temporal measurement of oropharyngeal swallowing was performed. Each individual was observed during the swallowing of a 5 mL spoonful of food in puree consistency. The Spearman´s rank correlation coefficient test was applied.Results There was no correlation between G1 and IPR and PTT. There was weak correlation between G2 and the studied parameters.Conclusion The increase of TOTT in the stroke individual has weak correlation with increased time in the pharyngeal phase.

Objetivo Correlacionar o tempo de trânsito oral total (TTOT) com o início da resposta faríngea (IRF) e o tempo de trânsito faríngeo (TTF) no indivíduo, após acidente vascular cerebral (AVC).Métodos O estudo incluiu 61 exames de videofluoroscopia de deglutição de indivíduos após AVC hemisférico isquêmico. Destes, 28 eram do gênero masculino e 33 do gênero feminino, com faixa etária variando de 40 a 101 anos (média de 65 anos). Para análise dos resultados, os indivíduos foram divididos em dois grupos. O Grupo 1 (G1) constou de 17 indivíduos com tempo de trânsito oral total até 2000 ms, conforme normalidade, e o Grupo 2 (G2), de 44 indivíduos com tempo de trânsito oral total maior que 2000 ms. Foi realizada análise quantitativa da deglutição orofaríngea. Cada indivíduo foi observado durante a deglutição de uma colher de 5 ml com alimento na consistência pastosa. Foi aplicado o teste de correlação de Spearman.Resultados Não houve correlação entre o G1 e a IRF e o TTF. Houve fraca correlação entre o G2 e os parâmetros estudados.Conclusão O aumento do tempo de trânsito oral total no indivíduo após AVC possui correlação fraca com o aumento do tempo na fase faríngea.
Correlation between oral and pharyngeal transit time in stroke
Keywords: Stroke; Deglutition disorders; Evaluation; Quantitative analysis; Software; Acidente vascular cerebral; Transtornos de deglutição; Avaliação; Análise quantitativa; Software